The Perceptible Speed and Its Relation to Metamemory among Students of College Of Education for Pure Sciences\ Ibn Al-Haytham (Journal Of Educational and Psychological Researches, 2018)
The study aims to identify the metamemory and perceptual speed among College students, the correlation between metamemory and perceptual speed among College students, and to which extend does metamemory contribute to perceptual speed among College students. The sample consisted of group of students were selected randomly by the researcher from five-different disciplines at the college of education for pure sciences. To collect study data, the researcher utilized two scales: perceptual speed scale that has translated to Arabic language by (Al-Shraqawi, Al- Shaikh, and Nadia Abed Al-Salam (1993). The second scale is metamemory scale (2002) which has translated to Arabic by Abu Ghazal (2007). The results revealed that college students have a high level of metamemory and perceptual speed, and there is a correlation between metamemory and perceptual speed.